PELAKSANAAN KEGIATAN MENGHIMPUN DANA OLEH UNIT SIMPAN PINJAM SWAMITRA KOPERASI SAIL JAYA TERHADAP CALON ANGGOTA KOPERASI - Sipayung, Dina Faurine Br.; Firdaus, Firdaus; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Cooperatives are built to create businesses and services in creating family principles, cooperative businesses are businesses that are compatible with economic democracy, because in economic democracy there are elements of cooperative business. However, a number of cooperatives were indentified as practicing raising funds or receiving savings from the winder community. Savings and Loans Cooperatives specifically in their business activities receive savings (rasing funds) and channeling them, originating from and for their members or other cooperatives and/or their members. The cooperative uses the presence of prospective members who save their moner in the cooperative. By registering propective members as stipulated in applicable regulations. The purpose of this thesis is : first, to find out the implementation of fundraising activities for prospective cooperative members by the Sail Jaya Cooperative Swamitra Savings and Loan Unit. Second, the understanding of prospective members about cooperatives and businesses as well as the rights and obligations of prospective members. Third, to find out the responsibilities of the Sail Jaya Cooperative Swamitra Savings and Loans Unit for raising funds for prospective cooperative membersThis thesis research method uses the type of sociological legal research, research conducted by carrying out legal identification and how the effectiveness of the law applies in society. This research is descriptive. Source of data used are primary data and secondary data, which consists of primary legal materials, secondary legal materials, and tertiary legal materials, data collection techniques in this study by interview method, and literature review, after the data collected is then analyzed of conclusions.From the results of the research and discussion it can be concluded first that, the implementation of fundraising activities of prospective cooperative members by the Sail Jaya Cooperative Swamitra Savings and Loan Unit did not work as it should or did not comply with applicable regulations So that the need for legal responsibility given by the cooperative so that prospective members get legal certainty and get their rights and there is a strict action from the government of the City of Pekanbaru Cooperative Service.Keywords: raise funds – Prospective Member – Savings and Loan (USP) - Cooperatives